Labetalol-Induced Hepatotoxicity during Pregnancy: A Case Report - Anna Whelan; Joanna Izewski; Charles Berkelhammer; Jami Walloch; Helen H. Kay (Thieme Medical Publishers, Inc., 2020)
Background Drug-induced liver injury is a common cause of transaminitis, occurring in up to 5% of patients who are hospitalized for liver failure. In pregnancy, transaminitis is seen in conditions which may require expedited delivery. Case A 39-year-old G2P0010 at 272/7 weeks' gestation with chronic hypertension on labetalol was found to have elevated transaminases. Evaluation for preeclampsia, acute fatty liver, nonalcoholic steatohepatitis, cholelithiasis, infections, and autoimmune conditions were all negative. Labetalol was then discontinued, and liver biopsy was performed. After discontinuation of labetalol, her hepatitis improved, and she was discharged on hospital day 12 and went on to deliver at term. Conclusion Labetalol-induced hepatitis should be considered in the differential for transaminitis during pregnancy to prevent iatrogenic preterm delivery.